Identifying important persons in the promotion of positive behaviour support (PBS) in disability services: A social network analysis. Issue 4 (2nd October 2022) - Hayward, Brent A.; McKay-Brown, Lisa; Poed, Shiralee; McVilly, Keith
ABSTRACT: Background: Little is known about networks for positive behaviour support (PBS) in disability services. This study explores a PBS network to identify influential persons in its promotion and communication. Methods: Quantitative sociometric methods were used to identify persons who occupy positions of either boundary spanning (those that link people and groups) and/or opinion leadership (those that are sought for advice). Results: Nineteen persons were identified. Boundary spanners met all criteria for the position while opinion leaders did not. Conclusions: This is the first published study of a PBS network in disability services and provides insights into persons involved in its systemic promotion. Boundary spanners are effectively bridging the PBS network, yet persons seeking information about PBS are doing so from opinion leaders that do not display a requisite characteristic for this role. These results have implications for the wider utility of PBS within disability service systems.